2020
DOI: 10.1186/s13014-020-01495-6
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric consequences of image guidance techniques on robust optimized intensity-modulated proton therapy for treatment of breast Cancer

Abstract: Purpose: To investigate the consequences of residual setup error on target dose distribution using various image registration strategies for breast cancer treated with intensity-modulated proton therapy (IMPT). Materials and methods: Among 11 post-lumpectomy patients who received IMPT, 44 dose distributions were computed. For each patient, the original plan (Plan-O) and three verification plans were calculated using different alignments: bony anatomy (VPlan-B), breast tissue (VPlan-T), and skin (VPlan-S). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, not all facilities may be capable of daily CBCT, in which case, larger robustness criteria should be used on the initial nominal plan to account for the daily setup variation that will not be corrected by 3-dimensional (3D) imaging. Liang et al 11 found that breast target D95 was well maintained for various image registration techniques, except for patients where the bony anatomy was more than 2⁰ off or patients with breast edema. Daily CBCT or other 3D techniques allow better visualization of these changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all facilities may be capable of daily CBCT, in which case, larger robustness criteria should be used on the initial nominal plan to account for the daily setup variation that will not be corrected by 3-dimensional (3D) imaging. Liang et al 11 found that breast target D95 was well maintained for various image registration techniques, except for patients where the bony anatomy was more than 2⁰ off or patients with breast edema. Daily CBCT or other 3D techniques allow better visualization of these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of plan robustness considerations during proton treatment planning (21). Robust optimization has shown its effectiveness in ensuring target coverage with the existence of inter-and intra-fraction motions in proton therapy (34)(35)(36). However, the usual practice for motion compensation is adding a margin to the target volume in photon therapy, and robustness is rarely considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, inter-and intrafraction variations cannot be eliminated with the inevitable anatomical changes. Previous studies have reported various intraand inter-fraction variations in breast radiotherapy (14)(15)(16)(17)(18)36). Lee et al (14) reported that the median intra-fractional variations for free-breathing right-breast radiotherapy are −0.1 (range −4.2 to 3.6) and 0.6 (range −3.4 to 5.0) mm in the LR and AP directions, and the median inter-fractional variations are −0.7 (range −7.8 to 6.4) and 2.9 (range −16.9 to 9.4) mm in the LR and AP directions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 147 Not directly applied for intrafractional motion management, the robust optimization for intensity-modulated proton therapy was used to address residual setup errors. 148 …”
Section: Future Directionsmentioning
confidence: 99%